Understandings About Scientific Inquiry in a South African School Prioritizing STEM. Issue 1 (2nd January 2022) - Gaigher, Estelle; Hattingh, Annemarie; Lederman, Judith; Lederman, Norman
Abstract : This paper reports on a case study of South African Grade 12 learners' views about scientific inquiry. The study focuses on a non-fee-paying government school that receives curricular support and resources to specifically develop Science, Technology, Engineering and Mathematics (STEM) teaching in a low socioeconomic setting. Data were collected using the Views About Scientific Inquiry (VASI) questionnaire. The learners demonstrated high levels of understanding of some inquiry aspects, while other aspects were poorly understood. The best understood aspects relate to questions, data and conclusions, whilst the aspects related to multiple methods, previous knowledge and differences in interpretations were poorly understood. Results were compared with those of Grade 12 learners at other South African schools who also completed the VASI questionnaire. The findings suggest that the case study school's emphasis on STEM and high performance may support understandings of scientific inquiry in general, but at the same time encourages some naive views such as believing that scientific investigations are rigid processes, independent of human creativity.